Exploration of Deep Ocean Ferromanganese Nodule Fields Using Radon as a Tracer. Issue 22 (15th November 2022) - Guo, Xiaoyi; Xu, Bochao; Yu, Huaming; Burnett, William C.; Li, Sanzhong; Lian, Ergang; Zhu, Zenghui; Zhao, Shibin; Chen, Guangquan; Duan, Xiaoyong; Dimova, Natasha; Wang, Yanni; et al.
Abstract: Ferromanganese nodules (Fe‐Mn nodules) are considered as potential sources of in‐demand metals (such as manganese, cobalt, nickel, copper, and rare‐earth elements) that are used in high‐technology industries. The resource potential of Mn nodules in the world ocean remains uncertain due to technological and financial challenges. Here we propose an effective tracer: the natural radioactive radon isotope ( 222 Rn) to assess the abundance of Fe‐Mn nodules on the sea floor. Significant linear relationships were observed between benthic excess 222 Rn fluxes and concentrations with Fe‐Mn nodule occurrence and coverage on the global seafloor. Benthic excess 222 Rn flux >10 7  dpm/m 2 /yr or bottom water 222 Rn concentrations >2, 000 dpm/m 3 indicate the possibility of Fe‐Mn nodules occurrence at >80% and seabed coverage of >25%. Our results indicate radon, relatively easy to measure, could serve as a novel and efficient tool for targeting Fe‐Mn nodule resources in the global abyssal ocean. Plain Language Summary: Ferromanganese nodules (Fe‐Mn nodules) are source of critical and rare metal for high technology industries. They are found on the abyssal plains of the deep oceans, but their abundance distributions are not well known. Here we proposed a more efficient method to locate Fe‐Mn nodule deposits and asses abundance of Fe‐Mn nodule field by measuring bottom water 222 Rn. Bottom water 222 Rn was mapped globally and found to overlap well with the distribution of the Fe‐Mn nodules. Benthic excess 222 Rn flux and concentration were linearly increased with the probability and ocean floor coverage of Fe‐Mn nodules occurrence. Other processes, including molecular diffusion, biological activity, and deep ocean currents are not sufficient to support the measured near bottom 222 Rn. This method is time‐saving and cost‐effective, most importantly, occurrence and abundance of the Fe‐Mn nodules can be quantitatively estimated via benthic ex 222 Rn flux or bottom water 222 Rn activity. Key Points: A significant positive linear relationship was found between the probability of Mn nodule occurrence and the benthic ex 222 Rn flux ( r  = 0.95) Benthic ex 222 Rn flux was linearly correlated with the percentage of the ocean floor coverage by Fe‐Mn nodules ( r  = 0.93) Surplus of ex 222 Rn flux can be a robust monitor to pinpoint locations and assess abundance of Fe‐Mn fields in the global deep ocean